BALI TOUR OBJECT VISUALIZATION USING MULTIMEDIA ASYMETRIX TOOLBOOK 4.0 - Teguh Imam Santoso; Yuce Yulina, SKom, MM (Jurnal Sistem Informasi, 2001)
Multimedia is a concept and new technology in the field of information technology. Where text, images, sound, animation and video incorporated into the computer to be stored, processed and presented on a linear or interactive.The Birth of Multimedia technology is a result of the advancement of electronic technology, computers and software. So with this multimedia technology will change the human task becomes easier.